The Development of Problem-Based Practicum Module to Learn Reaction Rate and Basa-Acid Solution - Puspasari Puspasari; Indri Astuti; Dede Suratman (STKIP Singkawang, 2018)
This study aims to determine the design, stages, and acquisition of student learning by using a practicum-based problem module on the material of reaction rate and acid-base solution. The development model used was a combination of the steps of Borg and Gall development research and Dick and Carey learning model design including needs analysis, design, initial design review, individual trials, revision, developing prototypes, small group trials, revision of finalization and trials field. Data collection techniques are observation, interviews, questionnaires and documentation with data collection tools for learning outcomes tests, observation sheets and questionnaires. Data analysis uses qualitative analysis and quantitative analysis. The results of the study show that the practicum module design is feasible to use, it can be seen from the module evaluation by experts that shows the module has met the eligibility criteria. In addition, field trials showed a positive response to the use of modules. Student learning after using the practicum module shows that students can actively use modules in practical activities. It can be seen from the t-test which shows that the value of t counts ≥ t table which means there are differences in learning outcomes before and after using the practicum module. The acquisition of attitude and skill aspects also showed very good results. So it can be concluded that the practicum module in learning the reaction rate and acid-base solution can help students to more easily learn the material of reaction rate and acid-base solution.